Transient natural convection in a partially open trapezoidal cavity filled with a water-based nanofluid under the effects of Brownian diffusion and thermophoresis - Bondareva, Nadezhda S.; Sheremet, Mikhail A.; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Emerald Publishing, 2018)
Purpose: The purpose of this paper is to study about the natural convection of water-based nanofluid in a partially open trapezoidal cavity under the influence of Brownian diffusion and thermophoresis. Design/methodology/approach: Governing equations formulated in dimensionless stream function – vorticity variables – have been solved by finite difference method with a homemade code C++. Effects of Rayleigh number (Ra = 50-1,000), Lewis number (Le = 10-1,000), buoyancy-ratio parameter (Nr = 0.1-5.0), Brownian motion parameter (Nb = 0.1, 1.0) and thermophoresis parameter (Nt = 0.1, 1.0) on nanofluid flow and heat transfer have been studied. Findings: It is found that high values of Rayleigh and Lewis numbers lead to the homogenization of nanoparticles distributions. For high values of Nt and Nb, heating is more essential and the cavity average temperature rises. Originality/value: The originality of this work is to analyze natural convection in an open-sided trapezoidal cavity with Brownian diffusion and thermophoresis. © 2018, Emerald Publishing Limited.
Keywords: Brownian diffusion; Nanofluid; Natural convection; Partially open trapezoidal cavity; Thermophoresis